Do black/white differences in telomere length depend on socioeconomic status?. (2nd October 2019) - Needham, Belinda L.; Salerno, Stephen; Roberts, Emily; Boss, Jonathan; Allgood, Kristi L.; Mukherjee, Bhramar
ABSTRACT: Social and economic disadvantage are hypothesized to increase the risk of disease and death via accelerated biological aging. Given that US blacks are socially and economically disadvantaged relative to whites, health disparities scholars expected that blacks would have shorter telomere length–a biomarker of cell aging–than whites. Yet the majority of studies have found that blacks have longer telomere length than whites. Using data from the National Health and Nutrition Examination Survey (n = 3, 761; 28.3% non-Hispanic black, 71.7% non-Hispanic white), we found that leukocyte telomere length was 4.00% (95% CI: 1.12%, 6.87%) longer among blacks compared to whites in the full sample, but differences were greatest among those with lower SES (5.66%; 95% CI: 0.10%, 10.32%), intermediate among those with middle SES (4.14%; 95% CI: 0.05%, 8.24%), and smallest among those with higher SES (2.33%; 95% CI: −3.02%, 7.67%). These results challenge purely genetic explanations for race differences in telomere length and point to a potential social-environmental cause of longer telomere length in US blacks.